Open ended laboratory (OEL): associating comprehensive learning and skills for civil engineering student / Farah Wahida Mohd Latib, Nurul Aishah Abd Rahman and Muhammad Isha Ismail - Mohd Latib, Farah Wahida; Abd Rahman, Nurul Aishah; Ismail, Muhammad Isha (2016)
An open-ended lab is where students are given the freedom to determine and do their own experiments, instead of merely following the already set guidelines from a lab manual or elsewhere. OEL is one of the approach in Outcome-Based Education (OBE) in a way to promotes students to be more comprehensive in all aspect in learning. This paper highlights the OEL processes framework as supporting documents to enhance OBE results towards sustainable development in education. This approach helps to systematically fasilitate students-centerd learning to improve, embeded and monitor all skills required by civil enginering students such as generic skills. In this paper, the focus of the Program Outcomes for this OEL approach, level of openess that reflect to the procedure in teaching in the labooratory, the used of rubric provided was discused and the comparison is made between traditional way of conducting and implement of laboratory with the OEL concept in order to get the overview of the performance of the OEL implementation.